Estudo epidemiológico molecular de casos de recidiva de tuberculose na região metropolitana de Vitória-Espírito Santo - Dettoni, Valdério do Valle (2005)
Tuberculosis is an infectious disease distributed throughout the world, transmitted by the respiratory route, with variable incidence and mortality rates related to socioeconomic status of the countries, being higher in low income countries. In spite of the effective therapy, recurrence of the disease can occur after cure or default, due to relapse or reinfection, worsening the disease load and increasing the annual risk of infection and the mortality and morbidity rates. In Brazil, there are few studies about tuberculosis recurrence. In relation to the role of reinfection as a factor contributing to recurrence, there are no studies in our country. In order to identify factors related to tuberculosis recurrence and evaluate the frequency of reinfection, we present a description of the epidemiological characteristics of 29 patients with TB recurrence treated in an outpatient reference clinic located in an intermediate incidence rate region. Patients were divided in 2 groups according to clinical and bacteriological criteria. A total of 85 M. tuberculosis strains, isolated of clinical specimens collected from these patients in two successive episodes of disease, were compared by the RFLP methodology and drug susceptibility tests. Due to the small number of patients included in this study, it was not possible to evaluate the statistical significance of the results. However, the results suggest a recurrence rate higher than the rate considered acceptable in the medical literature. Several factors are supposed to be related to tuberculosis recurrence, particularly HIV coinfection and other co-morbidities. Reinfection was detected in four patients. Among these, three were HIV co-infected of whom two had reinfection acquired multidrug resistance. Therefore, it is concluded that tuberculosis recurrence has a high frequency in this brazilian region. This is related to several factors, including the reinfection mechanism, which may be responsible for the transmission of multidrug resistance particularly in HIV co-infected patients. This fact requires more comprehensive studies in order to find more effective control measures of this disease.